Selective collection performance of an efficient quartz collector and its response to flotation separation of malachite from quartz. (1st October 2021) - Yang, Bin; Fu, Ya-Feng; Yin, Wan-Zhong; Sheng, Qiu-Yue; Zhu, Zhang-Lei; Yin, Xue-Ming
Highlights: LAEO-15 exhibited better selectivity for removing quartz from malachite than DA. LAEO-15 could be strongly adsorbed onto quartz instead of malachite. Electrostatic repulsion prevented LAEO-15 from being adsorbed onto malachite. Reverse flotation separation of malachite from quartz could be realized by LAEO-15. Abstract: In this study, laurylamine ethoxylate with fifteen ethoxylate units (LAEO-15) was employed as a quartz collector for the recovery of malachite from quartz via reverse flotation. Its collecting performance and adsorption mechanism were evaluated by flotation tests and surface analyses. The results of flotation tests suggested that LAEO-15 had an intense ability to collect quartz instead of malachite, and displayed a high flotation selectivity, which promoted the significant floatability differences of both minerals. XPS confirmed that quartz adsorbed a much larger quantity of LAEO-15 than malachite, resulting in the selective collection of quartz with LAEO-15. Zeta potential and FTIR characterization further uncovered that the strong adsorption of LAEO-15 was driven by hydrogen bonding and electrostatic attraction, while electrostatic repulsion hindered the LAEO-15 adsorption on the surface of malachite. As a result, the effective separation of malachite and quartz was realized with 20 mg/L LAEO-15 at pH 6.30 via reverse flotation, in which 92.54% of malachite was recovered and 92.72% of quartz was removed, coupled with a high SI value of 12.57 in concentrate. Therefore, compared with conventional collector dodecylamine, LAEO-15 exhibited high selectivity and purification effectiveness for the separation of malachite from quartz.